Preparation and Characterization of Ascorbic Acid Microcapsules Based on Gelatin Extracted from Tilapia Scale - Li, Peng; Ri Shen, Xuan (Asian Journal of Chemistry, 2014)
Gelatin extracted from tilapia scale (FSG) is used to encapsulate ascorbic acid under ultrasonic to demonstrate that FSG is a promising wall material in microencapsulation. The microcapsules are prepared with 15 mg/mL of gelatin and factors including concentration of transglutaminase and ascorbic acid, amount of emulsifier and temperature of solidification that related to the encapsulation rate are studied. Finally, the microcapsule with the highest encapsulation rate of 81.17 % is spheroid with average particle size of 5.73 μm. The ascorbic acid retention in the microcapsule is 53.39 % at 5 °C and 5.79 % at 25 °C after 30 days of storage. While at 37 °C, it is only 10 h, the encapsulation rate of ascorbic acid reaches 41.08 %. Thus, controlled-release without phase separation is followed with time elapsed and could be adjusted by storage temperature. Gelatin extracted from tilapia scale is an applicable wall material in microencapsulation and the microcapsule has real potential to be used in pharmaceuticals and cosmetic industry.